Digitalization and international competitiveness: A cross-country exploration of the relation between firm-level ICT use, productivity and export - Mark Vancauteren; Kevin Randy Chemo Dzukou; Michael Polder; Pierre A. Mohnen; Javier Miranda (National Bank of Belgium, 2024)
We study the relationship between ICT, total factor productivity and export at the firm level in Belgium, France and the Netherlands. In particular, we look at whether ICT has both a direct effect on export and an indirect effect via productivity improvements. We allow for endogeneity, unobserved heterogeneity, dynamic feedback, initial conditions and correlations between the time-invariant random effects and between the idiosyncratic random effects. We find similarities but also differences in the effects of ICT on export between the three countries.
Keywords: C23; D24; F14; O30; 330; ICT; productivity; export; firm data; panel data; international comparison